The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/medicina55080470
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Nature Microtubule Inhibitor Ivalin Induces G2/M Arrest and Apoptosis in Human Hepatocellular Carcinoma SMMC-7721 Cells In Vitro

Abstract: Background and Objectives: Microtubules are an attractive target for cancer chemotherapy. Previously, we reported that Ivalin exhibited excellent anti-migration and anti-invasion activities in human breast cancer cells. Here, we examined the microtubule inhibition effect of Ivalin in human hepatocellular carcinoma SMMC-7721 cells. Materials and Methods: We used the 3-(4,5-dimethylthiazol)-2,5-diphenyltetrazolium bromide (MTT) assay to evaluate the cell proliferation effect of Ivalin and flow cytometry analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Our previous studies confirmed that Ivalin (Figure 1) was significantly cytotoxic to SMMC-7721 cells (IC50: 4.34 ± 0.10) with a lower effect toward the normal cell line HL7702 (IC50: 25.86 ± 0.87) [13]. In response to characterizing the cell growth inhibition effect of Ivalin, we monitored morphological changes in SMMC-7721 cells after 24 h of treatment.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Our previous studies confirmed that Ivalin (Figure 1) was significantly cytotoxic to SMMC-7721 cells (IC50: 4.34 ± 0.10) with a lower effect toward the normal cell line HL7702 (IC50: 25.86 ± 0.87) [13]. In response to characterizing the cell growth inhibition effect of Ivalin, we monitored morphological changes in SMMC-7721 cells after 24 h of treatment.…”
Section: Resultssupporting
confidence: 58%
“…In our previous work, we reported the ideal microtubule depolymerization activities of Ivalin in SMMC-7721 cells [13]. In this study, we found that Ivalin treatment may lead to obviously apoptotic features including apoptotic body formation and nuclear condensation in the same cells.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Studies have shown that Aberrant KIF20A expression might independently predict poor overall survival and recurrence-free survival of hepatocellular carcinoma [27]. CCNB1 is a cycle-like protein that regulates cell cycle G2/M, and its expression imbalance is one of the causes of malignant tumor proliferation, including HCC [28]. Researches show that disease-free survival in the high PLOD2 expression group of HCC patients was significantly shorter when compared with the low-expression group [29].…”
Section: Discussionmentioning
confidence: 99%